PENGARUH RISIKO KREDIT DAN TINGKAT KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN SEKTOR BUMN YANG TERDAFTRA DI BEI PERIODE 2012-2016 - Ependi Ependi; Suhikmat Suhikmat (Jurnal Manajemen FE-UB, 2019)
The purpose of this study was to examine the effect of Credit Risk and Capital AdequacyLevel on Profitability (ROA) in SOE Sector Banking Companies Listed on the Indonesia StockExchange in 2012-2016. There are 43 Indonesian banking companies listed on the IndonesiaStock Exchange. Samples were taken 4 banking companies. The sampling technique used in thisstudy was purposive sampling.The independent variables studied were Credit Risk and Capital Adequacy Level while thedependent variable was Profitability (ROA). Secondary data in the form of financial statementsfor the period 2012-2016. The tool used to test hypotheses is a multiple linear regression test withthe help of SPSS Version 20 program.The t test results show that credit risk has a negative and significant effect on profitability(ROA), and the level of capital adequacy has a positive and significant effect on profitability(ROA). And the F Test Result, shows that there is a significant influence between Credit Risk(NPL) and the Capital Adequacy Level (CAR) together on Profitability (ROA). This can be seenfrom the magnitude of the coefficient of determination together which is 0.648. This shows thatthe influence of the independent variable on the dependent variable of 64.8%, the remaining35.2% is another factor outside of credit risk and the level of capital adequacy. The correlationtable shows that the results of the correlation coefficient 0.805 or 80.5%. This means that themagnitude of the correlation together has a very strong relationship.Keywords: Credit Risk, Capital Adequacy Level, Profitability (ROA).